Making flowers speak: Petrarch and idiorrhythmy - Southerden, F (Taylor and Francis, 2021)
This article brings Petrarch’s (1304–74) lyric poetry into dialogue with Barthes’s notion of “idiorrythmie” (idiorrhythmy) as outlined in his lecture course Comment vivre ensemble (How to Live Together). It explores both the idiorrhythmic aspects of Petrarchan desire and the traits of lyric utterance through which they are expressed, with a focus on canzone 126 of Petrarch’s Rerum vulgarium fragmenta (Fragments of Vernacular Things). The article begins with a study of Barthes’s exposition of idiorrhythmy: its medieval origins in the monastic communities of Mount Athos and the productively unstable and improvised character of the “living together,” and apart, that it implies. Most significant for the analysis that follows is idiorrhythmy’s relationship to eros, Barthes’s idea that idiorrhythmy preserves a space for the body’s desires in opening to interruptions, deviations, and digressions. The remainder of the article offers a close reading of Petrarch’s Rvf 126, focusing on one image in the poem that, like Barthes’s idiorrhythmy, is rooted in fantasy and embraces errancy: the image of a flower that turning and falling around the poet’s beloved seems to speak of love.